The Petrology and Petrochemistry of Andesite and Dacite Volcanoes in Eastern Bay of Plenty, New Zealand - Duncan, Andrew Rae (1970)
The volcanic rocks of Edgecumbe, Whale Island, White Island and Manawahe are andesites and dacites, which are collectively termed the Bay of Plenty volcanics. Edgecumbe is a comparatively young volcano, being active between 1700 and 8000 years B.P.; Whale Island has probably been inactive for at least the last 36,000 years; White Island has probably been active for much of the late Pleistocene, and is still in a stage of solfataric activity with intermittent tephra eruptions; and Manawahe is probably of the order of 750,000 year old (K-Ar date by J.J. Stipp). The geology of Edgecumbe, Whale Island and White Island is discussed, and the petrography and mineralogy of the Bay of plenty volcanics is discussed and compared. The rocks of Edgecumbe and Whale Island are extremely similar petrographically, but the rocks of White Island and Manawahe are sufficiently different that they can be distinguished both from one another and from Edgecumbe and Whale Island rocks. Most of the Bay of Plenty volcanics are plagioclase andesites or plagioclase dacites. New total rock analyses for 28 elements in 44 samples of the Bay of Plenty volcanics are presented, together with analyses of 4 samples from elsewhere in the Taupo Volcanic Zone. Three samples were analysed for an additional 17 elements. The Bay of Plenty volcanics are calc-alkaline and are predominantly dacites (greater than or equal to 63% SiO2) by Taylor et al.'s (1969) definition, but there is chemical continuity from samples with about 61% SiO2 to samples with about 66% SiO2. Major and trace element variation trends cannot be explained entirely by a crystal fractionation hypothesis, and assimilation of upper crustal material of rhyolitic composition best explains the variation trends for Edgecumbe and Whale Island. The variation trends and certain element abundances in White Island rocks suggest the assimilation of marine sediments, and introduction of seawater into the magma. Taken as a whole, the Bay of Plenty volcanics fit the chemical trends which have been ...